1995
DOI: 10.1002/em.2850260108
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus frequency in spleen lymphocytes from severely malnourished rats during lactation

Abstract: The purpose of this ex vivo study was to determine if severe malnutrition increases the frequency of micronuclei in spleen lymphocytes of experimentally malnourished rats during lactation. Micronucleus frequencies were analyzed in binucleate cells produced by the cytokinesis block method. The overall micronucleus frequency was significantly higher in binucleate cells from malnourished rats (21.30/1000) as compared to that observed in control rats (11.50/1000). The number of binucleate cells with more than one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
9
0
3
Order By: Relevance
“…The increases in MN-RETs observed in UN rats were in agreement with previously reported results that measured MN frequency and found that lymphocytes from UN children have increased MN frequencies in binucleate cells [Ortiz et al, 1997]. Another study has shown that spleen lymphocytes from UN rats during lactation have increased MN frequencies [Ortiz et al, 1995]. Furthermore, protein-calorie malnutrition experimentally produced during lactation increases the frequencies of spontaneous and MMC-induced MN-RETs in rat peripheral blood [Ortiz et al, 2004].…”
Section: Discussionsupporting
confidence: 91%
“…The increases in MN-RETs observed in UN rats were in agreement with previously reported results that measured MN frequency and found that lymphocytes from UN children have increased MN frequencies in binucleate cells [Ortiz et al, 1997]. Another study has shown that spleen lymphocytes from UN rats during lactation have increased MN frequencies [Ortiz et al, 1995]. Furthermore, protein-calorie malnutrition experimentally produced during lactation increases the frequencies of spontaneous and MMC-induced MN-RETs in rat peripheral blood [Ortiz et al, 2004].…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding, we (Friedrisch et al, 2008) and others (Betancourt et al, 1995;Ortiz et al, 1995) have already reported that nutrition factors can affect genomic stability either in diseased or healthy states. Antioxidant and folic acid deficiency has been extensively shown to increase DNA damage in children and adults.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies that have measured micronuclei found that lymphocytes from malnourished children have increased MN frequencies, analyzed in binucleate cells, and a greater susceptibility to MMC-induced damage [Ortiz et al, 1997]. Using similar methodology, spleen lymphocytes from rats malnourished during lactation had increased MN frequen- cies [Ortiz et al, 1995]. The MN assay has advantages over other methods as a measure of genotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…These studies indicate that malnutrition increases susceptibility to chromosome damage, as measured by chromosomal aberrations [Alu and Murthy, 1993], sister chromatid exchange [Ortiz et al, 1994], and micronuclei [Fenech, 1993;Ortiz et al, 1995].…”
Section: Introductionmentioning
confidence: 87%